2015
DOI: 10.3390/biomedicines3030224
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of IL-10 and CD4+CD25hi+ Treg Cells in Endemic Burkitt’s Lymphoma Patients

Abstract: Background: The interplay between Epstein-Barr virus infection, malaria, and endemic Burkitt’s Lymphoma is not well understood. Reports show diminished EBV-specific Th1 responses in children living in malaria endemic areas and deficiency of EBNA1-specific IFN-γ T cell responses in children with endemic Burkitt’s Lymphoma (eBL). This study, therefore, examined some factors involved in the loss of EBNA-1-specific T cell responses in eBL. Methods: T-cell subset frequencies, activation, and IFN-γ- or IL-4-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Based on the mechanisms of immuneescape developed by latency I (EBNA-1) cells, established after primary EBV infection, a cause-effect association between EBV infection and the disease onset in a subgroup of ME/CFS patients, could be hypothesized. Accordingly, IL-10 released by both EBV-transformed B cells and Tregs would favor a Th2 type immune response (43), and gp42-mediated disruption of TCR-MHC-II interaction would further decrease CD4 T cell activation, leading to poor CD4 T cell immunity to mitogens and other specific antigens, which have been described in some patients with ME/CFS (2). All these immune evasion m e c h a n i s m s t r i g g e r e d b y l a t e n t c e l l s i n d u c e a n immunodeficiency that allows EBV-transformed B cells, especially EBV latent I cells, to escape from immune surveillance.…”
Section: A Hypothetical Association Between Ebv and Me/cfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the mechanisms of immuneescape developed by latency I (EBNA-1) cells, established after primary EBV infection, a cause-effect association between EBV infection and the disease onset in a subgroup of ME/CFS patients, could be hypothesized. Accordingly, IL-10 released by both EBV-transformed B cells and Tregs would favor a Th2 type immune response (43), and gp42-mediated disruption of TCR-MHC-II interaction would further decrease CD4 T cell activation, leading to poor CD4 T cell immunity to mitogens and other specific antigens, which have been described in some patients with ME/CFS (2). All these immune evasion m e c h a n i s m s t r i g g e r e d b y l a t e n t c e l l s i n d u c e a n immunodeficiency that allows EBV-transformed B cells, especially EBV latent I cells, to escape from immune surveillance.…”
Section: A Hypothetical Association Between Ebv and Me/cfsmentioning
confidence: 99%
“…Both have been detected during the lytic phase in Burkitt lymphoma (latency I), suggesting that soluble gp42 is generated during EBV lytic infection and inhibits the presentation of HLA-II restricted antigens to T cells ( 40 ). Noteworthy, EBNA-1 specific cytotoxic CD4 T cells are decreased in patients with post-transplant lymphoproliferative disorders ( 41 ), in some pediatric forms of Burkitt lymphoma ( 42 , 43 ), in EBV-positive lymphoma ( 44 ), in lymphomas associated with HIV infection ( 45 ), and in lymphoma infiltrating the central nervous system ( 45 ). By contrast, the immune response in healthy individuals is sufficient to control EBV infection ( 35 , 46 ).…”
Section: Immunopathobiology Of the Epstein-barr Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion in CD39+ CD4+ immunoregulatory T Cells was observed in HTLV-1 infected patients and correlated with severity of neurological disorders 28. High levels of CD4+CD25hi+ Treg cells were recorded in endemic Burkitt’s lymphoma patients, a condition associated with EBV infection 29. Treg cell frequency significantly increased in EBV-associated gastric carcinomas tissues compared to EBV-negative gastric carcinomas tissues 30.…”
Section: Cancer and “High Treg” Infections Are Strongly Associatedmentioning
confidence: 98%
“…Tumor micro-environment, host immunity and systemic in ammatory response are the key factors that determine the clinical course and prognosis of tumor patients. More and more studies found tumorassociated macrophages (TAMs) are associated with poor clinical prognosis of a variety of tumors, including colon cancer, thyroid cancer and Burkitt's lymphoma by promoting angiogenesis, local invasion and metastasis [8][9][10]. Moreover, it has been con rmed that the growth and survival of malignant T cells depend on alternatively activated (M2) macrophages in micro-environment, and the growth of alternatively activated (M2) macrophages are affected by TAMs [11][12].…”
Section: Introductionmentioning
confidence: 99%